Navigating the bumps in the road: a narrative inquiry into the lives of low-income, non-traditional African American women community college students - Douglas, Adrian Henderson, author; Davies, Timothy, advisor (Colorado State University. Libraries, 2008)
The purpose of this narrative inquiry was to examine the lives of four women to see how they made sense of their socioeconomic backgrounds, past educational experiences, and educational journeys. The women were asked questions pertaining to their experiences surrounding socioeconomic status (SES) and education to determine what role these factors and habitus played in their decisions to enroll in higher education. Interpretive analysis allowed the researcher to see how participants attributed meanings to their experiences. No less than three in-depth interviews were conducted with each woman. All of the women were low-income, African American, single mothers who attend or attended community college. Their ages ranged from 26 to 53 years of age. The findings provided a greater understanding of what has taken place in the women's lives. Regarding SES, the women reflected on their childhood SES, their woes with welfare, and their view of education as the key to a new life. The findings surrounding education revealed dramatic changes in the women including increased self-worth and greater social awareness. The women are using education to reclaim their power, and create educational legacies for their children. Habitus and its various components make up a large part of who these women are. Thus habitus plays a tremendous role in the educational journeys of these women. Cultural capital consisted of their foundations. Social capital comprised their relationships. Human capital included their investments in education and economic capital covered their financial situations. Each area affected these women's educational journeys in some way, be it positively or negatively. The findings further addressed the women's educational foundations, personal responsibility, and the way they faced societal injustices to explain how this brought them to the decision to enroll in higher education. Living through poverty, racism, and discrimination helped these women realize that they needed to make changes in their lives. Each believed education was the key to a new life, so each chose to enroll in higher education. This study has implications for social service departments, K-12 school districts, community colleges, and other low-income, non-traditional African American women.
Keywords: African-American; community college; low-income; narrative inquiry; nontraditional students; women students; community college education; black studies; women's studies; inquiry method; African Americans; college students; African-American studies